Experimentally characterising the temperature and rate dependent behaviour of unfilled, and glass microsphere filled, natural rubber. (27th March 2023) - Trivedi, Akash R.; Whybrow, Rory; Muhr, Alan H.; Siviour, Clive R.
Abstract: Low-impedance, elastomeric materials are widely used in engineering applications where they are subjected to impact loading leading to high strain rate deformation. The strong rate and temperature dependence that is exhibited by these polymers and their composites provides further motivation for a deeper understanding of this complex behaviour including the interaction between the matrix and filler materials. In this paper, unfilled and glass microsphere filled natural rubbers are used as model materials to better understand the behaviour of low-impedance particulate composites. These materials were characterised experimentally over a range of strain rates and temperatures. The effect of filler volume fraction and mean particle diameter on the rate and temperature dependence of the overall mechanical response was also investigated, as well as damage evolution based on post-deformation analysis of interrupted compression experiments. In this paper, experimental insights and data are presented and discussed, which will influence future constitutive modelling efforts. Graphical abstract: Image 1 Highlights: Filled and unfilled natural rubber is extensively characterised in compression. Time-temperature superposition is used to compare strain rate and temperature dependence. Damage formation and residual strength are considered.